The use of aquatics in orthopedic and sports medicine rehabilitation and physical conditioning - Wilk, K. E.; Joyner, D. M. (SLACK Incorporated, 2014)
"The Use of Aquatics in Orthopedic and Sports Medicine Rehabilitation and Physical Conditioning" is a definitive and scientifically based text on the use and application of aquatic methodologies in both rehabilitation and physical conditioning appropriate for the general population to the elite athlete. "The Use of Aquatics in Orthopedic and Sports Medicine Rehabilitation and Physical Conditioning" represents a new generation of rehabilitation that is informative enough to be injury and sports specific. Dr. Kevin E. Wilk and Dr. David M. Joyner, along with noted domestic and international leaders in the field, explore the aquatic techniques and principles detailed in the work, while presenting this scientifically based material in an understandable and user-friendly format. Ten chapters take the reader from the history of aquatic rehabilitation and progress to discuss all parameters of aquatic rehabilitation. Some chapter topics include: - Theory and applications of aquatic therapy, - Pool selection, facility design, and engineering considerations, - Rehabilitation for the upper and lower extremities and spine, - Sports-specific training, - Research evidence for the benefits of aquatic exercise - Appendices, including 4 specific protocols for various lesions and disorders. "The Use of Aquatics in Orthopedic and Sports Medicine Rehabilitation and Physical Conditioning" represents a new era in the use and development of aquatic therapy in sports medicine rehabilitation and is perfect for physical therapists, athletic trainers, strength and conditioning coaches, personal trainers, and sports medicine professionals alike. (Klappentext)